PENGARUH RESTRUKTURISASI ORGANISASI DAN PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Ramadani, Yuli Ashaniais; Mahmud, Amir; Sellong , Abbas (AkMen JURNAL ILMIAH, 2025)
This study aims to examine the influence of organizational restructuring and work supervision on employee performance with job satisfaction as an intervening variable at PT. PLN (Persero) Regional Main Unit of Bangka Belitung. The data in this study were obtained from employees of PT. PLN (Persero) Regional Main Unit of Bangka Belitung in 2025 who were willing to participate as respondents. This study used primary data by conducting direct field research by administering questionnaires and drawing samples using the census method, where the sample was the entire population because the population only consisted of 95 employees. Data analysis techniques were carried out using descriptive statistical analysis and PLS (Partial Least Squares). Based on the hypothesis testing results, it can be concluded that organizational restructuring and work supervision have a positive and significant effect on employee performance, both directly and through job satisfaction as an intervening variable. Effective organizational restructuring improves task clarity, work efficiency, and employee motivation, which in turn positively impacts both satisfaction and performance. Similarly, effective work supervision through monitoring, evaluation, and constructive feedback makes employees feel appreciated and supported, ultimately encouraging them to work more optimally. Therefore, organizational restructuring and work supervision are crucial factors that must be strategically managed by PT. PLN (Persero) Regional Main Unit of Bangka Belitung to enhance job satisfaction and employee performance sustainably.